Knowledge and practices about rabies at Basic Health Units in Brazil (Research, Society and Development, 2022)
Objective: to map the pattern of spatial distribution of knowledge and vaccination practices regarding zoonosis rabies in the population assisted in Basic Health Units in the municipality of Birigui, São Paulo, Brazil. Method: analytical, non-experimental observational epidemiological study with a cross-sectional design. 400 questionnaires were randomly applied between January and July 2019 to the participants of the 10 Basic Health Units in the city of Birigui. The Kernel Density Estimator was used in the spatial analysis. Results: 74.25% (n=297) of the participants are female, 44% (n=176) were between 31-50 years of age, and 67% (n=268) of the population correctly pointed the animals rabies transmitters. Clusters with higher densities of knowledge and practices in Basic Health Units were identified, as well as the most vulnerable. Conclusion: Spatial analyzes contributed to a more specific assessment of the profile of knowledge of residents about rabies.